Effect of cumulus cells and β-mercaptoethanol supplement during in vitro maturation on bovine oocyte competency / Nor Azlina Abd. Aziz - Nor Azlina , Abd. Aziz (2019)
The oocyte source of livestock animals in eastern tropical region was relatively scarce and of unknown history, with the low-quality oocytes outnumbered the good quality. Hence, there was a need to develop more objective criteria or indicators for oocyte selection and modification of the microenvironment to improve the outcome of bovine in vitro embryo production. The objective of the study was to investigate the effects of: I) different groups of bovine oocytes according to the compactness of cumulus cells and II) β-mercaptoethanol (BME) supplement (50, 100, 150 and 200 μM) during in vitro maturation (IVM), on a) early apoptosis; b) intracellular GSH contents; c) oocyte maturation rate, and d) cleavage and subsequent embryo development rates after in vitro fertilisation (IVF). Bovine oocytes were retrieved from local slaughterhouses and classified into three groups, namely, Groups A (compact and dense cumulus cells), B (compact but less dense cumulus cells) and C (thin or little remnant of cumulus cells); and subsequently cultured in vitro in CO2 (5%) in air at 38.5ºC in humidified atmosphere. Early apoptosis in oocytes before and after maturation was assessed using Annexin-V staining and GSH contents using GSH assay. Maturation rate, i.e. resumption to metaphase II was evaluated using Giemsa staining. Embryo development was assessed for 9 days after IVF. Analysis of Variance, Duncan’s Multiple Range Tests and Independent T-test were used to analyse the data. The findings of Experiment I: cumulus cells influenced early apoptosis rates and GSH contents before and after in vitro maturation of bovine oocytes. In vitro maturation increased rates of early apoptosis and intracellular GSH was synthesised during maturation only in Group A oocytes. The compactness of cumulus cell layers exerted no effect on the bovine oocyte maturation rate after IVM. Cumulus cells promoted early embryo development up to 16-cell stage. In Experiment II, BME supplement during IVM increased GSH synthesis and early apoptosis in oocytes with less compact cumulus cells (Groups B and C) contradictory to Group A oocytes. In a nutshell, supplementation of BME in IVM medium did not exert any effect on oocyte developmental competency of good quality oocytes, except the addition of 50 μM BME increased maturation rate of Group A oocytes. The supplementation of BME above concentration 100 μM appeared to be detrimental to early embryo development. Group A oocytes, considered as good quality oocytes, with compact and dense cumulus cells, displayed a particular characteristic compared with Groups B and C. β-mercaptoethanol supplement during IVM played a role in promoting some factors in oocytes with less cumulus cells (Groups B and C). It is recommended that a specific in vitro embryo production protocols and procedures be established for the different bovine oocyte groups.